Public or Private Foreign Funds to Spur Sustainable Human Development - (:unkn) unknown (My University, 2012)
This study is meant to bring a contribution to the debate of foreign public versus private funds effectiveness. Using multivariable regression, our study explores the impact of FDI, ODA and corruption on Human Development Index (HDI) in low middle income countries of two regions: Asia and Africa. We find that FDI and ODA inflows have significant positive impact on HDI in Asia, but the effect of foreign aid (ODA) is stronger than the impact of FDI on this indicator. In contrast, the level of corruption doesn't affect human development index in Asia. As for Africa, FDI inflows impact significantly HDI. However, the foreign aid (ODA) appears not to be related to African HDI level. Moreover, the freer the region is from corruption, the higher positive evolution of HDI. Our results are interesting, especially with regard to total amount of foreign capital flows received in both analyzed regions. The Asian countries have been successful in efficient use of received capital for human development matters. On the contrary, African countries haven't taken advantage of foreign aid to improve their population living standards. Our study confirms the need to combine the private and public foreign investment to make sure that all activities sectors are covered, including education and health.
Keywords: African Research